“You’re not learning skills—you’re just realizing what you can do”: a preliminary study of self-regulation in higher education - Nyman, Fredrik (Frontiers in Education, 2024)
This preliminary study employs a phenomenological approach to investigate the phenomenon of self-regulated learning among higher education students in the United Kingdom. The research identifies both facilitators and challenges associated with effective self-regulated learning. Through indepth interviews and thematic analysis, key themes such as motivation, the learning process, support systems, planning, and group dynamics emerge.Noteworthy findings include the importance of clear guidelines regarding study hours and designated learning environments for students.Furthermore, educators are encouraged to integrate activities fostering learning strategies and promoting social relationships within student groups.The study highlights the necessity for additional tools and support mechanisms, even for students who exhibit autonomous motivation, to enhance their effectiveness in self-study practices.